Planear las comidas: para una buena nutrición - Isabel Valentín-Oquendo; Claudia Peñuela (EDIS)
Do you ask yourself, “What’s for dinner tonight?” Planning meals helps you save time, money, and energy. When you write out your meals, it is easier to see if your family is eating a variety of food choices, nutrient-dense foods, and the right amounts of foods for good nutrition. This revised 1-page Spanish-language fact sheet was written by Isabel Valentin-Oquendo and Claudia Peñuela and published by the UF Department of Family Youth and Community Sciences, May 2011.